Size characterization and detection of aerosolized nanoplastics originating from evaporated thermoplastics. Issue 2 (24th December 2021) - Wlasits, Peter Josef; Stoellner, Andrea; Lattner, Gregor; Maggauer, Klara; Winkler, Paul Martin
Abstract: In recent years, a growing number of studies investigated the presence of micro- and nanoscopic particles in the environment originating from commonly used plastics. Pathways into the environment and generation mechanisms are still not well understood. Controlled generation methods of particles from macroplastics are required to enable research of the fundamental processes governing the dispersion of these particles in the environment. Here, we present the results of a study focusing on the generation and characterization of aerosol nanoparticles from macroplastics using a tube furnace. Three common thermoplastics were used as particle material: Polyethene (PE), Polypropene (PP) and Polyethylene Terephthalate (PET). Commodity versions of these materials were compared to higher-purity versions. The produced particles were size characterized using a Differential Mobility Particle Sizer. Furthermore, we investigated the activation of particles from PET in Condensation Particle Counters by measuring the 50% cutoff diameters. The results could be directly compared to previous measurements using other organic seed particles. Our study provides crucial insights into the effects governing the production of aerosolized nanoparticles from thermoplastics at comparatively low temperatures. We therefore expect our study to act as basis for further research toward a thorough understanding of the physicochemical processes governing nanoparticle production from plastic materials. Eventually this may lead to new detection methods of nanoplastics in airborne state and allow for quantification of airborne nanoplastic concentrations.